Aerobic Exercise Alleviates the Impairment of Cognitive Control Ability Induced by Sleep Deprivation in College Students: Research Based on Go/NoGo Task - Liu, Shangwu; Zhang, Runhong (Frontiers in Psychology, 2022)
ABSTRACT: The purpose of this study was to investigate the effects of moderate intensity aerobic exercise on cognitive control ability of college students after sleep deprivation in a timely manner, and to provide an experimental basis for occupational groups who often work night shifts to effectively respond to cognitive control ability impairment caused by sleep deprivation. Thirty healthy college students (15 males) were studied for one night of sleep deprivation and one night of normal sleep (8 h) using a group randomized crossover design, and the go/no-go task paradigm was used to compare the changes in various performance indicators between the two states. Afterwards, 30 subjects were randomly divided into exercise sedentary rest (control group) group after experiencing a night of sleep deprivation at the same time, the exercise group completed a 30-min moderate-intensity aerobic exercise, and each group performed a Go/Nogo task at different time points after exercise (0 min, 30 min and 1 h) to compare the changes in various performance indicators in the two states. The results showed that complete sleep deprivation for one night could severely impair cognitive control in both response inhibition and response execution, but this impairment could be effectively alleviated by a 30-min aerobic exercise, and the time course benefits produced by physical exercise could last until 1 h after exercise. Physical exercise can be used as an effective emergency measure to maintain cognitive control ability in regular night shift groups in addition to restorative sleep. Keywords: college students, aerobic exercise, sleep deprivation, cognitive control